Pengukuran Produktivitas Dalam Meningkatkan Hasil Produksi Menggunakan Metode Objective Matrix Dan Pendekatan Root Cause Analysis - Fahrul Huda; Ayudyah Eka Apsari (JURNAL ILMIAH RESEARCH STUDENT, 2024)
. PT. IGP Internasional Bantul is a company engaged in manufacturing. This company produces several custom barbies. Product production level at PT. IGP International Bantul is very high. The problem is that the company has not achieved the production targets that have been set. In 2022 to 2023, in several months, namely August 2022, the target number was 4,454,588 pcs for a month, but 4,333,029 pcs were produced. This research aims to determine the level of productivity measurement at PT. IGP International Bantul uses the OMAX method and identifies factors that can influence productivity in the production of Barbie clothes at PT. IGP International Bantul using the RCA method. The data processing stage is carried out at PT. IGP International Bantul by identifying types of problems using the Objective Matrix (OMAX), Root Cause Analysis with weighting based on the Analytical Hierarchy process (AHP) method. So the largest productivity value was obtained in July 2022, namely 135%, while the lowest productivity index was in February and April 2023, namely -35%. Then to find the root of the problem in the company using the Root Cause Analysis (RCA) method. The tools to find the root of the problem used in the RCA method are the 5-why and fishbone diagrams which produce two main problems, namely lack of training for operators and lack of maintenance on machines.